Contractual liability for abuse of the right - Abdel Sahib, Assistant Professor Dr. Ali Mutashar (The college of law and political science journal, 2023)
If the theory of abuse of the right is currently one of the stable theories in the study of responsibility for a harmful act, a closer its capabilities application in the field of abuse of contract rights or based on its consideration of the applications of the principle of good faith in the field of contracts in its restrictive function, which necessitates a study of the abuse of the right in the doctrinal field, its consequences, and the position of, its legislative applications, the various laws on all that.